Developmental aspects of entrepreneurship [electronic resource] - Bhargava, Shivganesh , 1959- (Los Angeles, Calif : Response Books, 2007)
In Indian context
Description based on print version record
Includes bibliographical references and index
Keywords: Entrepreneurship